Long‐term chemical evolution and modification of continental basement brines – a field study from the Schwarzwald, SW Germany. Issue 3 (5th April 2016) - Walter, B. F.; Burisch, M.; Markl, G.
Abstract: Highly saline, deep‐seated basement brines are of major importance for ore‐forming processes, but their genesis is controversial. Based on studies of fluid inclusions from hydrothermal veins of various ages, we reconstruct the temporal evolution of continental basement fluids from the Variscan Schwarzwald (Germany). During the Carboniferous (vein type i), quartz–tourmaline veins precipitated from low‐salinity (<4.5wt% NaCl + CaCl2 ), high‐temperature (≤390°C) H2 O‐NaCl‐(CO2 ‐CH4 ) fluids with Cl/Br mass ratios = 50–146. In the Permian (vein type ii), cooling of H2 O‐NaCl‐(KCl‐CaCl2 ) metamorphic fluids (T ≤ 310°C, 2–4.5wt% NaCl + CaCl2, Cl/Br mass ratios = 90) leads to the precipitation of quartz‐Sb‐Au veins. Around the Triassic–Jurassic boundary (vein type iii), quartz–haematite veins formed from two distinct fluids: a low‐salinity fluid (similar to (ii)) and a high‐salinity fluid (T = 100–320°C, >20wt% NaCl + CaCl2, Cl/Br mass ratios = 60–110). Both fluids types were present during vein formation but did not mix with each other (because of hydrogeological reasons). Jurassic–Cretaceous veins (vein type iv) record fluid mixing between an older bittern brine (Cl/Br mass ratios 80) and a younger halite dissolution brine (Cl/Br mass ratios >1000) of similar salinity, resulting in a mixed H2 O‐NaCl‐CaCl2 brine (50–140°C, 23–26wt% NaCl + CaCl2, Cl/Br mass ratios = 80–520). During post‐Cretaceous times (vein type v), the opening of the Upper Rhine Graben and the concomitant juxtaposition of various aquifers, which enabled mixing of high‐ and low‐salinity fluids and resulted in vein formation (multicomponent fluid H2 O‐NaCl‐CaCl2 ‐(SO4 ‐HCO3 ), 70–190°C, 5–25wt% NaCl‐CaCl2 and Cl/Br mass ratios = 2–140). The first occurrence of highly saline brines is recorded in veins that formed shortly after deposition of halite in the Muschelkalk Ocean above the basement, suggesting an external source of the brine's salinity. Hence, today's brines in the European basement probably developed from inherited evaporitic bittern brines. These were afterwards extensively modified by fluid–rock interaction on their migration paths through the crystalline basement and later by mixing with younger meteoric fluids and halite dissolution brines.